ANALISIS KARAKTER PEDULI LINGKUNGAN DAN HUBUNGANNYA DENGAN PENGUASAAN KONSEP EKOSISTEM DAN PERUBAHAN LINGKUNGAN PADA SISWA KELAS XI SMA N 1 PEKANBARU - Destati Simanjuntak; Yuslim Fauziah; Darmawati Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to (i) describe the character of environmental care students of class XI SMA N 1 Pekanbaru; (ii) to know the relationship between the character of environmental care and mastery of ecosystems concept; (iii) to know the relationship between the character of environmental care and mastery of environmental change concepts. This research was conducted in Juli-Agustus 2018. The sample in this study amounted to 50 students determined based on random sampling techniques.The instrument consisted of environmentally caring character questionnaires, description test of ecosystem and description test of environmental change. The data obtained were analyzed using the correlation test product moment at the level of 5%, test of determination, and descriptive analysis. The results of the study showed that (i) the character of the environmental care students of class XI of SMA N 1 Pekanbaru showed an average of 82.6% in the good category; (ii) there is a significant relationship between the character of environmental care and the mastery of ecosystem concepts of 0.676 with a strong category and the coefficient of determination (r2) is 0.457; (iii) there is a significant relationship between the character of environmental care and mastery of the concept of environmental change of 0.784 with a strong category, and the value of the coefficient of determination (r2) is 0.614. Based on the results obtained, it can be concluded that the character of environmental care students of class XI SMA N 1 Pekanbaru is included in the good category, there is a strong relationship between the two variables.Key Words: Ecosystem, Environmentally Caring Character, Environmental Change, Mastery Concepts